Base-catalyzed stereoselective thiosulfonylation of ynones for the facile synthesis of thio-functionalized vinyl sulfones. Issue 5 (24th January 2023) - Luo, Jinyun; Lin, Muze; Xia, Dengpeng; Du, Guangfen; Cai, Zhihua; Dai, Bin; He, Lin
Abstract : Brønsted base catalyzed thiosulfonylation and trifluoromethylthiosulfonylation of ynones produced thio-functionalized vinyl sulfones in high yields with excellent E -selectivity. Abstract : The first catalytic vicinal thiosulfonylation of ynones has been developed. Under the catalysis of 1–20 mol% Cs2 CO3, various ynones underwent the Michael addition/nucleophilic substitution tandem reaction with different thiosulfonates to form C–SO2 and C–S bonds simultaneously and produced thio-functionalized vinyl sulfones in high yields and with excellent E -selectivity. In addition, on using K3 PO4 as the base, ynones can couple with trifluoromethyl thiosulfonates through a similar tandem process to afford the corresponding trifluoromethylthiolated products in good to high yields with excellent stereoselectivity.